069 Introduction of a simple lumbar puncture pack to a busy medical admissions unit improves diagnosis of central nervous system infections. Issue 3 (9th February 2012) - Michael, B; Powell, G; Hatch, S; Bailey, L; Almond, S; Nightingale, S; Cousins, D; Hart, I J; Griffiths, M; Solomon, T
Abstract : Background: In patients with central nervous system (CNS) infections urgent diagnosis and treatment significantly reduces mortality and neurological morbidity. Cerebrospinal fluid (CSF) analysis, obtained by lumbar puncture (LP), is pivotal to the diagnosis. Recent studies have demonstrated that patients typically do not have the appropriate samples taken. Methods: We designed a LP pack including simple clinical guidelines and audited 6 months prior to and after the introduction of this in a busy medical admissions unit. Results: The screen identified 177 patients who had an LP; 93 before and 84 after the introduction of the pack; 52 and 41 patients had the LP for a suspected CNS infection respectively. CSF and paired plasma glucose were sent in more patients after the introduction of the LP pack than before [41 (100%) vs 43 (82%), p<0.05 and 41 (100%) vs 24 (46%), p<0.001]. More patients had CSF sent for virological studies [21 (51%) vs 8 (15%), p<0.001] and more had a virus identified [5 (12%) vs 1 (2%), p<0.05]. Additionally, pathogen identification was higher overall (7 (17%) vs 3 (6%) respectively p<0.01]. Discussion: The introduction of a simple LP pack in a busy medical admissions unit resulted in significant improvements in CSF investigations and improved diagnostic sensitivity in patients with suspected CNS infection.